Students’ improvement in performance, conception and interest on compound nouns learning via inomaj / Ahmad Afandi Yusri - Yusri, Ahmad Afandi (2020)
This study aims to investigate the usage of innovative flashcards called Inomaj to help students’ performance, conception, and interest in compound nouns learning. This study was conducted on year 1 students. This study is based on a quantitative method that was collected through classroom assessments, pre, and post-tests, observations, and questionnaires. Before the treatment session, students were given a Pre-Test to determine their performance in the classroom assessment. The student’s attitude during the treatment session was recorded by the observation method through the checklist. Post-tests were given to respondents after the treatment session ended. The questionnaire was conducted to collect information and feedback from them after using Inomaj. All data obtained is analyzed based on the content analysis approach. The findings show that the usage of Inomaj is effective to improve their performance in compound nouns learning. The post-tests result showed about 83% improvement. Similarly, students also interest to learn and able to conceptualize compound nouns.